Building a tool to overcome barriers in research-implementation spaces: The Conservation Evidence database. (October 2019) - Sutherland, William J.; Taylor, Nigel G.; MacFarlane, Douglas; Amano, Tatsuya; Christie, Alec P.; Dicks, Lynn V.; Lemasson, Anaëlle J.; Littlewood, Nick A.; Martin, Philip A.; Ockendon, Nancy; Petrovan, Silviu O.; Robertson, Rebecca J.; et al.
Abstract: Conservation practitioners, policy-makers and researchers work within shared spaces with many shared goals. Improving the flow of information between conservation researchers, practitioners and policy-makers could lead to dramatic gains in the effectiveness of conservation practice. However, several barriers can hinder this transfer including lack of time, inaccessibility of evidence, the real or perceived irrelevance of scientific research to practical questions, and the politically motivated spread of disinformation. Conservation Evidence works to overcome these barriers by providing a freely-available database of summarized scientific evidence for the effects of conservation interventions on biodiversity. The methods used to build this database – a combination of discipline-wide literature searching and subject-wide evidence synthesis – have been developed over the last 15 years to address the challenges of synthesizing large volumes of evidence of varying quality and measured outcomes. Here, we describe the methods to enhance understanding of the database and how it should be used. We discuss how the database can help to expand multi-directional information transfers between research, practice and policy, which should improve the implementation of evidence-based conservation and, ultimately, achieve better outcomes for biodiversity. Highlights: Conservation effectiveness could be improved by integrating evidence and practice. Evidence synthesis helps practitioners by collating multiple studies into reviews. Conservation Evidence aims to review conservation actions for all taxa and habitats. We describe the holistic search and synthesis methods used to build the database. The database could help overcome barriers between research, practice and policy.